Impact of the European Carbon Border Adjustment Mechanism (CBAM) on the German industry - Juan Diego Martinez (Junior Management Science (JUMS), 2024)
The European Commission's proposal for a Carbon Border Adjustment Mechanism (CBAM) aims to address carbon emissions in imports to the EU. This thesis researches the financial implications for exporting countries due to CBAM's implementation, focusing on how it may alter production costs, demand dynamics, and global trading relationships. Using a quantitative research approach, the study analyzes existing carbon market landscapes and Germany's trade ties with non-European exporters in key sectors like iron, steel, aluminum, polymers and chemicals. It evaluates CBAM guidelines and assesses potential weaknesses in determining embodied CO2 emissions. Results suggest CBAM may not drastically shift production costs or demand patterns immediately. China, with inherent cost advantages, may maintain competitiveness, while India's advantages could diminish by 2035. However, uncertainties persist on CBAM's long-term impact on global trade dynamics. The analysis highlights CBAM's uneven financial burden across exporters, influenced by energy structures and production technologies. Weaknesses in CBAM's calculation methods are highlighted, recommending standardized guidelines to ensure accurate emissions reporting. This study prompts policymakers to evaluate CBAM's effectiveness in meeting climate goals while maintaining global trade equity.
Keywords: 650; CBAM; carbon pricing; corporate ESG; decarbonization; European Carbon Border Adjustment Mechanism